(untitled) (Itinera, 2024)
The aim of this article is to show the interrelationship between, memory, language and artistic production in the reflections of Paul Valéry. If some of Valéry’s essays in this sense were already accessible to readers, the recent publication of the almost entirely unpublished materials of the Cours de Poétique – held at the College de France from 1937 to 1941 – reveals a fruitful theoretical laboratory that can provide numerous insights into Valéry’s reflections on poetic production and the aesthetic importance of observing memory and its role in the creation of artistic forms.